Wormian Bones and Dilated Scalp Veins in an Infant With Epilepsy - Randhawa, Manjinder (J Pediatr Neurosci, 2019)
A three-months boy presented with recurrent seizures. On examination, he was fair, had dilated scalp veins, sparse hypopigmented hair, and was hypotonic. X-ray of the skull showed wormian bones. The child was diagnosed with Menkes disease. The manuscript aims to emphasize dilated scalp veins in diagnosis of Menkes disease.